Investigation of stress and heat strain in asphalt workers - Mohammad Hosein Beheshti; Roohallah Hajizadeh (Gonabad University of Medical Sciences, 2017)
Heat stress is one of the harmful factors in workplaces. Asphalt workers are exposed to thermal stress due to the open environment and process. The aim of this study was to assess the heat stress and strain in asphalt workers. This study was conducted on 29 employees of asphalt workstation. The heat stress was measured based on Wet-Bulb Globe Temperature (WBGT). Also, physiological parameters such as blood pressure and heart rate of asphalt workers were measured. The mean of WBGT index for drivers of asphalt machinery, trowels, shovels people and burner servicemen were 27.77, 27.77 and 29.61°C respectively whereas this value was 29.81, 29.85 and 3.23°C for workers of asphalt workstations respectively. The process of asphalting has significant effect on heat stress and physiological parameters of individuals. The pearson correlation between WBGT and heart rate, systolic blood pressure and diastolic blood pressure was significant. Asphalt workers are exposed to heat stress caused by different sources which may generate a host of heat strains in these people so special attention should be paid to control heat stress.